Role of intermittent pneumatic compression in the treatment of breast cancer–related lymphoedema: a randomized controlled trial. (February 2020) - Tastaban, Engin; Soyder, Aykut; Aydin, Elif; Sendur, Omer Faruk; Turan, Yasemin; Ture, Mevlut; Bilgen, Mehmet
Objective: To evaluate the role of intermittent pneumatic compression in the treatment of breast cancer–related lymphoedema. Design: Randomized controlled trial. Setting: Physical medicine and rehabilitation clinic at a university hospital. Subjects: Seventy-six patients with lymphoedema. Interventions: Patients were allocated into Group 1 (complex decongestive treatment, n  = 38) and Group 2 (complex decongestive treatment + intermittent pneumatic compression, n  = 38). The complex decongestive treatment involved skin care, manual lymphatic drainage, compression bandaging, and exercise for 20 sessions. Group 2 additionally received intermittent pneumatic compression. Main measures: Quantitative outcomes consisted of volumetric measures prior to and after the treatment. Clinical assessments included severity of pain, heaviness and tightness, disability, grip strength, and depression. Results: Lymphoedema was similar at baseline, but treatments significantly reduced the excess volume (from 373 mL to 203 mL in Group 1 and 379.5 mL to 189.5 mL in Group 2). Percentage excess volumes (PEVs) decreased in both groups. The percentage reduction of excess volume was better in Group 2 than Group 1, but the intergroup difference was not significant. The clinical scores reflected improvements, but the heaviness and tightness read significantly lower in Group 2 than Group 1. Conclusion: Intermittent pneumatic compression seems to add no benefit when combined with complex decongestive treatment of lymphoedema, but, may be functional in reducing the sensations of heaviness and tightness for the patients with pitting oedema.